INTERNATIONAL EDUCATIONAL COOPERATION AS AN INSTRUMENT OF SOFT POWER IN THE GUEST LECTURE BETWEEN DR. SOETOMO UNIVERSITY, SURABAYA AND OKAYAMA UNIVERSITY, JAPAN IN 2023 - Paramita Maulidya; Suhartawan Budianto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze how the Guest Lecture program between the University of Dr. Soetomo (Unitomo) andOkayama University in 2023 functions as an instrument of soft power in Japan’s educational diplomacy inIndonesia. Using a qualitative-descriptive approach, the research explores the mechanisms of value transmissionand cultural influence embedded within cross-border academic collaboration. The findings reveal that the academicpartnership operates not through coercive means, but rather through persuasive approaches grounded in academicreputation, institutional credibility, and interpersonal trust. The Guest Lecture program effectively fosters students’motivation and aspirations to pursue higher education in Japan by providing scholarship information, accessibleEnglish-language international programs, and active alumni engagement. Moreover, it cultivates positivebehavioral changes among students, including discipline, professionalism, and work ethics values that reflectJapanese cultural principles. The study concludes that higher education serves as a strategic channel of soft power,strengthening bilateral relations between Indonesia and Japan through the internalization of shared educationalvalues. It recommends transforming the Guest Lecture into a structured and sustainable annual program,emphasizing collaborative research and alumni network development as strategic steps to enhance the long-termbenefits of academic diplomacy for both universities.Keywords: soft power, educational diplomacy, academic cooperation, guest lecture, Japan–Indonesia relations